2018
DOI: 10.1016/j.heliyon.2018.e00728
|View full text |Cite
|
Sign up to set email alerts
|

Operating room staff and surgeon documentation curriculum improves wound classification accuracy

Abstract: BackgroundMisclassification of wounds in the operating room (OR) can adversely affect surgical site infection (SSI) reporting and reimbursement. This study aimed to measure the effects of a curriculum on documentation of surgical wound classification (SWC) for operating room staff and surgeons.MethodsAccuracy of SWC was determined by comparing SWC documented by OR staff during the original operation to SWC determined by in-depth chart review. Patients 18 years or older undergoing inpatient surgical procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…8 The authors demonstrated improved accuracy, although, after implementation, over 40% of cases were still misclassified by surgeons and allied health providers alike. 3,[6][7][8] The CDC offers little guidance by stating "The wound class must be applied according to the wound class schema that is adopted within each organization." 3 In addition to concerns with application, there is potential for errors with interpretation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…8 The authors demonstrated improved accuracy, although, after implementation, over 40% of cases were still misclassified by surgeons and allied health providers alike. 3,[6][7][8] The CDC offers little guidance by stating "The wound class must be applied according to the wound class schema that is adopted within each organization." 3 In addition to concerns with application, there is potential for errors with interpretation.…”
Section: Discussionmentioning
confidence: 93%
“…Currently, no standardized method of documentation of SWC exists among institutions; thus, the SWC is notoriously misidentified by surgeons and operating room nurses. 3,[6][7][8] For a classification system to be useful, it must be predictive and reliable. Historical data established a correlation between increasing SWC and postoperative complications, but nearly all of these studies were based on visceral tissue procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many were found to have mucositis during surgery and some had mucoid or purulent effusions (Table III). Wounds were classified as contaminated or dirty 20 in the majority of patients. Many had prior surgery on the operated ear.…”
Section: Resultsmentioning
confidence: 99%
“…Class I or clean wound includes injuries that are infectionfree, although current bacteria on the skin contaminate the injury [50]. Class II or clean-contaminated wound involves injuries, which affect the respiratory and digestive system, characterized by no loss of tissue fluid [51]. Class III or contaminated wound contains non-purulent inflammation and class IV or dirty/infected wound contains purulent inflammation [52].…”
Section: Complexity Of Cutaneous Lesions and Skin Regeneration Processmentioning
confidence: 99%